MENJADI BERAGAMA: KONVERSI AGAMA DAN RELASI KUASA PADA INDIGENOUS COMMUNITY - Laila Sari Masyhur (At-Tafkir, 2014)
Using a theory of power relation of Michel Foucault, the followingresearch analyze the behavior of religious conversion in the indigenouspeople of Anak Rawa in Penyengat, Siak District, hereinafter referred toas the native People. The research will show that in the middle of thedomination of the state and theologians, the community of indigenouspeople actualizes power to maintain its identity in the the midst of theinvasion of new values and culture. To support the argument, theresearcher traced the religiousity of the Indigenous People focusing onseveral events of everyday life such as traditions of marriage, death, andcelebration of religious holidays. In addition to adapting to fies the ritualtraditions of each religion so that thes traditions become a means ofpreserving their communal identity as a native tribe. The researchultimately shows the interplay between the state and theologians as thedominant group, on the one hand, and the indigenous community as asubjugated group, on the other, in the use of power.